Interfacial width and phase equilibrium in polymer-fullerene thin-films - Anthony Higgins (Communications Physics, 2019)
Domain composition and interfacial structure are critical factors in organic photovoltaic performance. Here, we report neutron reflectivity, grazing-incidence X-ray diffraction and atomic force microscopy measurements of polymer/fullerene thin-films to test a hypothesis that these partially miscible blends rapidly develop composition profiles consisting of co-existing phases in liquid-liquid equilibrium. We study a range of polymer molecular weights between 2 and 300 kg mol−1, annealing temperatures between 120 and 170 oC, and timescales up to 10 min, yielding over 50 distinct measurement conditions. Model bilayers of fullerene-derivatives and polystyrene enable a rigorous examination of theoretical predictions of the effect of polymer mass and interaction parameter on the compositions, ϕ, and interfacial width, w, of the coexistent phases. We independently measure ϕ and w and find that both Flory-Huggins mean-field-theory and key aspects of self-consistent-field-theory are remarkably consistent with experiment. Our findings pave the way for predictive composition and interface design in organic photovoltaics based on simple experimental measurements and equilibrium thermodynamic theory.